Continuous wound infiltration or epidural analgesia for pain prevention after hepato-pancreato-biliary surgery within an enhanced recovery program (POP-UP trial): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Mungroop, Timothy; Veelo, Denise; Busch, Olivier; van Dieren, Susan; van Gulik, Thomas; Karsten, Tom; de Castro, Steve; Godfried, Marc; Thiel, Bram; Hollmann, Markus; Lirk, Philipp; Besselink, Marc
Abstract Background Postoperative pain prevention is essential for the recovery of surgical patients. Continuous (thoracic) epidural analgesia (CEA) is routinely practiced for major abdominal surgery, but evidence is conflicting on its benefits in this setting. Potential disadvantages of epidural analgesia are a) perioperative hypotension, frequently requiring additional intravenous fluid boluses or prolonged use of vasopressors; b) relatively high failure rates, with periods of inadequate analgesia; and c) the risk of rare but serious, at times persistent, neurologic complications (hematoma and abscess). In recent years, continuous (subfascial) wound infiltration (CWI) plus patient-controlled analgesia (PCA) has been suggested as a safe and reliable alternative, which does not have the previously mentioned disadvantages, but evidence from multicenter trials targeting a specific surgical population is lacking. We hypothesize that CWI+PCA is equally as effective as CEA, without the mentioned disadvantages. Methods/design POP-UP is a randomized controlled noninferiority multicenter trial, recruiting adult patients scheduled for elective hepato-pancreato-biliary surgery via laparotomy in an enhanced recovery setting. A total of 102 patients are being randomly allocated to CWI+PCA or (P)CEA. Our primary endpoint is the Overall Benefit of Analgesic Score (OBAS), a composite endpoint of pain intensity, opioid-related adverse effects and patient satisfaction, during postoperative days 1 to 5. Secondary endpoints include length of the hospital stay, number of patients with severe pain, and the use of rescue medication. Discussion POP-UP is a pragmatic trial that will provide evidence of whether CWI+PCA is noninferior as compared to (P)CEA after elective hepato-pancreato-biliary surgery via laparotomy in an enhanced recovery setting. If this hypothesis is confirmed, this finding could contribute to more widespread implementation of this technique, especially when the described disadvantages of epidural analgesia are less often observed with CWI+PCA. Trial registration Netherlands Trial RegisterNTR4948 (registry date 2 January 2015).